Uma Máquina de Processos de Desenvolvimento de Software Baseada em Agentes Inteligentes - Murta, Leonardo Gresta Paulino; Werner, Cláudia Maria Lima (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
The objective of this work is to provide an architecture based on intelligent agents that allows to execute and control software processes. The use of intelligent agents provides a more pro-active and dynamic architecture, differentiating it from the traditional static approaches, which are mainly based on state transition diagrams. In this approach, a modeled process is represented by Prolog predicates stored in a knowledge base, and used throughout process execution and control. The knowledge base represents the current state of the process and it is explored by intelligent agents which are responsible for maintaining the correct flow of process execution, informing developers about possible activities that can be done, tools that can be used, etc. Moreover, to support process management, measurements such as team productivity can be performed by the agents and informed to the project manager.